Women's Myths and Misconceptions as Barriers to Contraceptive Use: A Comparative Study: Mitos dan Kesalahpahaman di Kalangan Perempuan sebagai Hambatan dalam Penggunaan Kontrasepsi: Sebuah Studi Komparatif - Amal Fadil Noori Radi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Contraceptive use remains a central component of reproductive health, yet persistent myths continue to hinder its adoption globally. Specific Background: In Iraq, despite the availability of family planning services, misconceptions about contraception remain widespread, contributing to unmet needs and high fertility rates. Knowledge Gap: Limited comparative evidence exists on how these misconceptions vary across different Iraqi regions and cultural contexts. Aims: This study aimed to assess the prevalence of contraceptive myths among multiparous women and examine regional differences in perceptions across three Iraqi cities. Results: Findings revealed high levels of misconceptions, particularly related to menstrual disruption (66.4%), body changes (64.6%), and complexity of use (65.6%). Over half of participants endorsed beliefs about fertility risks and health concerns. Significant regional differences were observed, with higher levels of health-related concerns and religious opposition in Karbala. Social media emerged as the primary information source, while reliance on healthcare professionals remained limited. Novelty: The study provides a comparative regional analysis highlighting the persistence of misconceptions despite relatively high educational attainment. Implications: These findings underscore the need for culturally tailored educational interventions, improved provider communication, and evidence-based information dissemination strategies to address misinformation and support informed contraceptive decision-making. Keywords: Contraception, Reproductive Health, Misconceptions, Cultural Factors, Regional Differences Key Findings Highlights High prevalence of false beliefs related to menstrual and physical effects Strong regional variation linked to cultural and religious context Dominance of non-medical information channels in shaping perceptions